AN ANALYSIS OF FIGURATIVE LANGUAGE IN THE SONG LYRIC “TERI DDOOBHANA” - Dr. Vijay Kumar (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2024)
This examination is troubling with the undeniable investigation of metaphorical language in the music verse "Teri Ddoobhana" by Sh. Narendra Singh Negi. The purpose of the test is to determine the types of figurative language used in the said one. Subjective graphic strategy used to order and separate sentences in tones. After a sentence is inserted into a musical verse, a different figurative language event appears. Seven types of non-literal languages ​​- simile, simile, metaphor, simulation, synecdoche, image and complex meaning - have been used to spread this musical verse. Keywords: Figurative language; Allusion, Personification, Synecdoche, Symbol, Oxymoron